(untitled) (Research, Society and Development, 2023)
Cholecalciferol (vitamin D3) is a lipophilic secosteroid hormone; the main source of obtaining derives from exposure of the skin to UVB radiation. Increasing studies have shown its broad spectrum of action, which go beyond mineral and bone homeostasis, but with significant activity in other systems, organs and tissues, due to the presence of its nuclear receptors (VDR) and its activating enzyme 1 alpha-hydroxylase (CYP27B1). Regarding the physiological dose and ideal serum levels, it remains under discussion. To associate it with nanotechnology is to seek to innovate and improve in the new pharmacological forms of therapy, which allows expansion for targeted, safe and efficient supplementation of this hormone, arising from the diversity of nanosystems. Studies are justified in order to provide bionanotechnology and its nanosystems with adequate cholecalciferol supplementation. The present article has as general objectives to demonstrate the applicability of bionanotechnology similar to cholecalciferol and to declare new possibilities combining science and quality in health; level with specific objectives, which are conducting a survey of techniques in nanotechnology for adequate and safe inclusion with cholecalciferol, in addition to presenting an innovative alternative in order to efficiently deliver the active ingredient in question. The scientific methodology used is a narrative bibliographic review, based on the exploratory research method and based on the three research sources. SciELO, PubMed and ScienceDirect databases were used. This baseline study is expected to be the precursor for development in practice in research laboratories, for future large-scale innovative applicability.